Teaching-service integration and social impact in 50 years of public health history School of Dentistry of the "Universidade Estadual Paulista Júlio de Mesquita Filho" - Nemre Adas Saliba; Orlando Saliba; Suzely Adas Saliba Moimaz; Cléa Adas Saliba Garbin; Renato Moreira Arcieri; Luiz Fernando Lolli (Faculdade São Leopoldo Mandic, 2009)
To verify the projects and programs developed during the course of 50-year history of School of Dentistry Aracatuba of the "Universidade Estadual Paulista Júlio de Mesquita Filho" (State of São Paulo -Brazil), in the public health area, in agreement with the dental models of attendance and considering the background and the progress of the Public Health policies in Brazil, with the aim of reporting on the experience of integrating teaching-service, professional education and the social impact. A documentary research of a descriptive nature was conducted, by consulting the institutional files of the Dental Faculty, considering; official texts, reports, documents, databases and publications, with reference to the period from 1957 to 2007. The descriptive analysis demonstrated that the main actions developed were: Campaign for home filters, Campaign for construction of Wells and Sewages, Campaign for Fluoridation of the Araçatuba and Area Water Supply, Epidemiologic Surveys, Extramural Dental services, Extension projects; Attendance to pregnant women, the elderly and children, Oral cancer prevention program, Program for Heterogeneous Fluoride control, Creation of master's degree program, Municipal health counselor training courses, Training of State of São Paulo Family Health Program community agents and teams, Advisory services to municipalities and production of didactic-pedagogic materials for health education. Several programs have been and are being developed, with successful health practices in the area, accompanying the progress of health policies and promoting professional education with integration of the university into the local health and community services.